Facing Diseases Caused by Trypanosomatid Parasites: Rational Design of Pd and Pt Complexes With Bioactive Ligands - Gambino, Dinorah; Otero, Lucía (Frontiers in Chemistry, 2022)
Human African Trypanosomiasis (HAT), Chagas disease or American Trypanosomiasis (CD), and leishmaniases are protozoan infections produced by trypanosomatid parasites belonging to the kinetoplastid order and they constitute an urgent global health problem. In fact, there is an urgent need of more efficient and less toxic chemotherapy for these diseases. Medicinal inorganic chemistry currently offers an attractive option for the rational design of new drugs and, in particular, antiparasitic ones. In this sense, one of the main strategies for the design of metal-based antiparasitic compounds has been the coordination of an organic ligand with known or potential biological activity, to a metal centre or an organometallic core. Classical metal coordination complexes or organometallic compounds could be designed as multifunctional agents joining, in a single molecule, different chemical species that could affect different parasitic targets. This review is focused on the rational design of palladium(II) and platinum(II) compounds with bioactive ligands as prospective drugs against trypanosomatid parasites that has been conducted by our group during the last 20 years.